Grammatical Errors in Students' Translating Text by the Informatics Department Students in Stekom Semarang (NOBEL: Journal of Literature and Language Teaching, 2018)
Abstract: The errors cannot be separated from the students who learn English as their Foreign Language in writing skills. They always make error, especially in grammar term. It is because of the difference between the Indonesian and English grammatical pattern. The purposes of this study are to find out the grammatical errors based on Dulay, Burt and Krashen's surface structure taxonomy that happen in students' writing text in translating text from Indonesian to English especially in using simple present tense and to find the sources of errors. Mix method,qualitative and quantitative, is used as the method in this study. The data is taken from 20 students of the third-semester students in Stekom Semarang. This study found that misformation is the highest errors, 96 errors or 54,8% from the whole errors. Next, 40 errors or 22,8% for addition errors, 29 errors or 16,5% for omission errors and 10 errors or 5,71% for misordering errors from the whole errors. Intralingual factor is the most source of learner errors. There are 75% of errors that caused by intralingual factor and 25% errors are caused by interlanguage factors. Keywords: error analysis; grammatical error; translating text; simple present tense; stekom semarang.